THE FACTORS OF CELLULAR REGULATION OF THE UTERUS CONTRACTIVE ACTIVITY BY PHYSIOLOGICAL ACT OF DELIVERY AND BY UTERINE INERTIA - M. G. Nekrasova; V. A. Kulakova; T. N. Pogorelova; N. A. Drukker; V. A. Linde (Медицинский вестник Юга России, 2013)
Purpose. To develop a method of prediction of primary uterine inertia on the basis of study of cytokine and vasoactive bioregulator content dynamics.Materials and methods. The material for the research was blood of women taken in the end of gestation (38-40 weeks) and also in the I period of delivery over time from 23 women with physiological act of delivery and from 19 – with uterine inertia.Results. By primary uterine inertia there is an increase of relaxin production by 2 times and a decrease of TNF-α production: before delivery – by 1.5 times, during delivery – by 2 times, relative to the data by physiological delivery. Differently directed changes of TGF-β1 and IL-1β content – increase of the first one and decrease of the second one – are one of the reasons of low generation of nitric oxide as a result of reduction of NO-synthase activity under the action of these cytokines. High level of relaxin neutralizes the endogenous oxytocin action and the decrease of TNF-α and nitric oxide production causes changes in the content of intracellular calcium in myometrium cells.Summary: The detected character of the intracellular regulation disturbance of the uterus contractive activity is a basis for the development of uterine inertia.